Karakterisasi Obat Nyamuk Bakar Herbal Dengan Bahan Baku Limbah Gagang Cengkeh dan Tempurung Biji Pala - Pebrywati Watimury; Rizky F. Latukau (Jurnal Biologi Papua, 2021)
The increase of of cloves and sed nutmeg productions effects in its waste into the environment. However, the cloves and nutmeg shell could be use as mosquito repellent. The combination of essential oil extracted from cloves and nutmeg shell functions well as repellent for mosquitos. This research aims to identified the characteristics of essential oil extracted from these two spices by analysing its water, carbon aand ash concentrate. Therefore, we found that water level in U1 was 1.4573, and U2 was 1.6070, hence ash rate for U1 was  7,8674, U2 was 7,49224 and for carbon it was U1 24,4496 U2 23,5778. At the end we could say that for and ash it has already meet the SNI standard, while carbon hasn’t meet SNI standard yet.  Key words: Herbal mosquito repellent; waste; nutmeg shell waste.